The Effect of Dzikir on Stress and Random Blood Sugar in Patients with Diabetes Mellitus - Nisbah, Novilia Qurotun; Harmayetty, Harmayetty; Dewi, Lingga Curnia (Universitas Airlangga, 2020)
Introduction: Diabetes Mellitus is one of the causes of stress on chronic diseases. Stress affects blood glucose control, compliance, treatment costs, and death. Dhikr is one of the therapeutic alternatives that can be used to reduce stress and blood sugar levels. The purpose of this study is to analyze the effect of dzikir on stress and random blood sugar in patients with diabetes mellitus.Method: The study used a quasi-experimental pre-test approach with control group design with a sample of 60 Diabetes Mellitus patients aged 40-60 years, divided into two groups of treatment group 30 people and intervention 30 people and using methods Purposive sampling. Variables consist of dhikr, stress and random blood sugar levels. This research uses Diabetes Distres Scale (DDS) Questionnaire instruments as well as glucometers to measure random blood sugar levels. The statistical test used was the Wilcoxon Signed Rank Test and the Mann Whitney Test with a significance of α â‰¤ 0.05.Results: The results showed that the level of stress before and after the administration of Dhikr in the treatment group had a difference in value with significance p = 0.000. Whereas on blood sugar levels random group treatment acquire significance value P = 0,047.Conclusion: Dhikr and prayer reduce stress and anxiety by helping individuals form perceptions other than fear that is the belief that any stressor can be dealt with well with the help of God. Dhikr affects stress and blood sugar in patients with diabetes mellitus. But in addition to dhikr, acceptance of diseases and compliance with treatment will maximize the treatment that is being lived